Marantodes pumilum var. alata Enhances Fracture Healing Through Gene Regulation in a Postmenopausal Rat Model - Tijjani Rabiu Giaze; Norazlina Mohamed; Syed Alhafiz Syed Hashim; Ahmad Nazrun Shuid; Ima Nirwana Soelaiman; Norliza Muhammad; Fadhlullah Zuhair Jafar Sidik; Jamia Azdina Jamal (Pharmaceuticals)
Background: Marantodes pumilum var. alata (MPva) has been reported to promote fracture repair. This study investigates the role of MPva leaf extract on biochemical markers and bone-repair genes in a postmenopausal rat model to understand its fracture-healing properties. Methods: Thirty female Sprague Dawley rats were grouped into sham-operated (Sham), ovariectomized control (OVXC), estrogen treatment (ERT), and plant treatment (MPv20 and MPv100) groups. After ovariectomy, the right tibiae of rats were fractured. The ERT group was treated with 64.5 μg/kg/day of estrogen, while the MPv20 and MPv100 groups received 20 and 100 mg/kg/day doses of MPva leaf extract, respectively, for 8 weeks. Sham and OVXC acted as untreated controls. Blood samples collected before and after treatment were assayed for pro-inflammatory cytokines (IL-6 and TNF-α), while bone samples were assayed for bone-turnover markers: osteocalcin and pyridinoline, oxidative-status markers (GPx, SOD, and MDA), and bone-repair genes (Bglap, Spp1, Dkk1, Igf1, Tnfsf11, and Fgf23). Results: IL-6, GPx, and SOD levels were significantly increased in both MPv groups (p < 0.05). IGF1 was significantly upregulated in both MPv groups, while Tnfsf11 was downregulated in the MPv20 group (p < 0.05). Conclusions: MPva leaf extract may promote bone repair by stimulating pro-inflammatory and antioxidant responses, which are associated with its regulation of Igf1 and Tnfsf11 genes.